Social Work in Republic of Buryatia - Tatyana Bazarova (Social Work and Society, 2003)
The Republic of Buryatia is situated in Eastern Sibiria, the eastern coast of Baikal Lake. The total area of the republic is 351 thousand square kilometers. The capital of Republic is Ulan-Ude. The modern social-economic situation in Russia is extremely paradoxical and multiaspectual – negative processes take place almost in all spheres of the society. The introduction of market economy principles, the process of privatisation, and the last economic crises in the Federation of Russia have brought many social phenomena - among them increasing poverty, homelessness and still high rate of unemployment are the worst one. It makes the changes in the state social welfare programmes and functioning patterns be implemented. Social problems are especially very important in the so-called “depressive” regions of Russia (Buryatia Republic is among those regions). The most important is the staff supplement of social services and the level of professionalism of people who work there. This problem consists of two aspects: first, the number of specialists with professional education of social workers is not enough; second, the level of professionalism of the workers is very low.